Following Up on Smallholder Farmers and Supermarkets in Kenya - Andersson, Camilla I.M.; Chege, Christine Gacheri Kiria; Rao, E.J.O.; Qaim, Matin (Wiley, 2015)
In many developing countries, supermarkets are expanding rapidly. This affects farmers’ marketing options. Previous studies have analyzed welfare effects of smallholder participation in supermarket channels from a static perspective, using cross‐section data. We develop a conceptual framework and use panel data to better understand participation and impact dynamics. The analysis focuses on vegetable producers in Kenya. Participation in supermarket channels is associated with income gains. However, many farmers have dropped out of the supermarket channel due to various constraints. The initial income gains cannot be sustained when returning to the traditional market. Organizational support may be needed to avoid widening income disparities.